Epilepsy in "Sunflower syndrome": electroclinical features, therapeutic response, and long-term follow-up. (December 2021) - Belcastro, Vincenzo; Casellato, Susanna; Striano, Pasquale; Capovilla, Giuseppe; Savasta, Salvatore; Foiadelli, Thomas; Sofia, Vito; Giuliano, Loretta; Riva, Antonella; Elia, Maurizio; Cesaroni, Elisabetta; Bonaventura, Carlo Di; et al.
Abstract: Background: Sunflower syndrome (SFS) is a rare childhood-onset generalized epilepsy characterized by photosensitivity, heliotropism, and drug-resistant stereotyped seizures maybe self-induced by hand-waving maneuvers. Data on the long-term prognosis are scantly and evidence over best treatment strategies is lacking. Methods: We retrospectively describe the electroclinical features, and therapeutic response in a group of 21 patients with SFS, without intellectual disability. Results: 16 patients were female (67%), with a median age at onset of 7 years. In all patients, ictal episodes began with sun-staring, and hand-waving in front of the sunlight, accompanied by brief typical absence seizures. 17 patients (81%) showed interictal EEG abnormalities, mainly characterized by spike and polyspike-and-wave discharges. Ictal epileptiform activity occurred approximately less than one second after the start of hand-waving. At the last follow-up (median length 8.2 years), 12 patients (57%) were drug-resistant. Nine of them (75%) achieved seizure control with the use of tainted lenses, either alone or compared with anti-seizure medications (ASM). Disappearance of seizures was associated with EEG improvement/normalization when tinted glasses were used during EEG recordings. Conclusion: While the clinical and EEG characteristics of SFS are well defined, the best therapeutic approaches are still under debate. Our data confirms a high rate of drug-resistance and frequent need of polytherapy. Of note, in drug-resistant patients, lenses (but not ASM) were able to suppress PPR in our patients while wearing lenses. Regarding the role of lenses, we do not only rely on the PPR reduction but also clinically by the reduction of seizures. Although additional data are needed, lenses seem to have a powerful potential role for the management of SFS.